GEORGIAN-ARABIC PALIMPSEST FROM DAGESTAN (BRIEF REPORT) - Gvanceladze, Tejmuraz Ionovic; Gvanceladze, Gvanca Tejmurazovna; Hapizov, Sahban Magomedovic (History, Archeology and Ethnography of the Caucasus, 2018)
Abstract. Georgian-Dagestan relations in the early Middle Ages were distinguished by their diversity. At the same time, they included both close political ties and cultural contacts, which became even closer up until the XIV century. This aspect was mainly reflected in the influence of medieval Georgia on the spread of Christianity, Georgian literature and language in Highland Dagestan (Avaria). One aspect of this cultural influence can be considered the spread of book culture and, in particular, Georgian manuscripts. Until recently, the message from Georgian sources was not confirmed in the form of identifying specific Georgian manuscripts, except for the detection of individual sheets. During the study in the Foundation of Oriental Manuscripts of the Institute of History, Archeology and Ethnography, we discovered a manuscript - the Georgian-Arab Palimpsest. This article provides a brief report - an analysis of this manuscript. The study of the Arabic text showed that we are dealing with a Sufi composition at the turn of the X-XI centuries, written in eastern Iran and rewritten no later than the XVII century in the mountainous Dagestan. Unfortunately, the colophon and the title page of the manuscript have not been preserved and we do not have specific information about the place and date of correspondence of the Arabic text. When writing the Georgian text, Asomtavruli font was used, which already speaks of the antiquity of the manuscript. Analysis of the content suggests that the Georgian text consists of non-canonical texts of the Gospels of Mark and Luke. The grammatical features of the text, namely the use of the so-called Khanmet verbs suggests that the text reflects the language situation before the disappearance of the Khanmet forms. That is, the text could be written exclusively from the second half of the VII century until the VIII century, i.e. before erasing the Khanmet forms of verbs.